Analisis Pengaruh Fraud Hexagon Model Terhadap Financial Statement Fraud : (Studi Kasus Perusahaan BUMN yang Terdaftar di BEI Sektor Infrastruktur Tahun 2020-2023) - I Gede Ngurah Wira Dharma; Edy Sujana; I Gede Putu Banu Astawa (Universitas Pendidikan Ganesha, 2026)
This study explored the application of the Fraud Hexagon Model in detecting indications of financial statement fraud among BUMN infrastructure companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. The model expands upon previous fraud theories by incorporating two additional elements, there are collusion and arrogance. That’s can bringing the total to six analytical components: financial stability, financial target, CEO’s educational background, involvement in government projects, ineffective supervision, auditor rotation, and the CEO's photo frequency in reports. Employing a quantitative, associative approach, this research relied on secondary data sourced from published annual reports. A purposive sampling method was applied, selecting nine BUMN firms and yielding 36 observations across four years. Statistical analysis was carried out using multiple linear regression through SPSS version 26. The empirical findings revealed that financial target, ineffective monitoring, auditor change, and frequent appearance of the CEO’s image positively and significantly influenced the likelihood of fraudulent financial reporting. In contrast, financial stability, government project involvement, and CEO education exhibited a significant negative correlation with such fraud